Study of the relationship of LDH/AST ratio with the probability of manifestation and duration of HELLP syndrome (multicenter longitudinal analytical clinical trial) - N. Yu. Pylaeva; D. N. Protsenko; Y. M. Shifman; O. V. Ignatenko; A. V. Kulikov; Yu. S. Raspopin; O. V. Ryazanova; N. V. Lishchenko; A. V. Pylaev; E. V. Sadovaya; E. N. Kazinina; K. A. Bozhenkov; et al. (Messenger of ANESTHESIOLOGY AND RESUSCITATION, 2026)
Introduction. HELLP syndrome is a life-threatening complication of preeclampsia with high rates of maternal and perinatal morbidity, which necessitates the development of reliable prognostic markers of its manifestation and duration. The article presents the results of a multicenter retrospective analytical clinical trial «HELLP-RU», dedicated to assessing the prognostic significance of the ratio of lactate dehydrogenase to aspartate aminotransferase (LDH/AST) in pregnant women with preeclampsia.The objective was to evaluate the association between the lactate dehydrogenase to aspartate aminotransferase ratio (LDH/AST) and both the likelihood of HELLP syndrome manifestation and the duration of its clinical course. Materials and methods . This study included 139 female patientы diagnosed with complete or partial HELLP syndrome (2018–2022, 16 clinical centers). Laboratory and clinical data were analyzed at three predefined time points: upon hospital admission, immediately prior to delivery, and during the postpartum period. Temporal changes in the LDH/AST ratio were examined in relation to timing of disease onset and overall disease duration. Results . The distribution of complete and partial forms of HELLP syndrome varied across the stages of clinical observation. Dynamic analysis of the LDH/AST ratio demonstrated statistically significant intergroup differences. Persistently low LDH/AST ratios (< 5) were associated with a prolonged clinical course of HELLP syndrome, whereas higher ratios (> 10) correlated with its short-term course. Notably, a decline in the LDH/AST ratio in the absence of overt clinical deterioration preceded clinical manifestation of HELLP syndrome. Conclusions . The study revealed that the LDH/AST ratio is an accessible prognostic marker of the manifestation and duration of HELLP syndrome, which is important for timely clinical management and reducing the incidence of adverse outcomes.